2023
DOI: 10.1002/fsn3.3355
|View full text |Cite
|
Sign up to set email alerts
|

The effect of chitosan coating combined with cold plasma on the quality and safety of pistachio during storage

Abstract: Pistachios are one of the most important agricultural and export products of Iran. Fresh pistachio fruit has soft skin, is highly perishable, and therefore has a short life after harvesting, which has made traders and consumers have a great desire to increase the shelf life of this product. For this purpose, in this study, the effect of different concentrations of chitosan as an edible coating (0.5 and 1.5% w/v) and the duration of cold plasma treatment (60 and 120 s) were investigated during 180 days of pista… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…As shown in the table, majority of the studies were carried out using dielectric barrier discharge (DBD) cold plasma treatment, where researchers like Rashvand et al [ 65 ], Goiana et al [ 72 ], Wu et al [ 77 ] and Chen et al [ 47 , 79 ] reported improvements in tensile strength, elasticity and barrier properties like water vapour and oxygen transmission rates. Enhanced stability and shelf life of packaging films and substrates were observed by Glicerina et al [ 67 ] and Akhavan-Mahdavi et al [ 68 ], and modified surface properties of composite materials were reported by Goiana et al [ 72 ] and Chen et al [ 79 ], where they noted changes in surface morphology and hydrophobicity depending on the type of film and plasma treatment frequency, with improved wettability, roughness, and surface free energy after coating or plasma treatment. Additionally, changes in film structure were observed by Wu et al [ 77 ] and Chen et al [ 47 ], while observing rearrangement of protein chains, slight changes in crystal structure, and improved packing density within the film structure.…”
Section: Plasma Technology In Food Packagingmentioning
confidence: 93%
See 2 more Smart Citations
“…As shown in the table, majority of the studies were carried out using dielectric barrier discharge (DBD) cold plasma treatment, where researchers like Rashvand et al [ 65 ], Goiana et al [ 72 ], Wu et al [ 77 ] and Chen et al [ 47 , 79 ] reported improvements in tensile strength, elasticity and barrier properties like water vapour and oxygen transmission rates. Enhanced stability and shelf life of packaging films and substrates were observed by Glicerina et al [ 67 ] and Akhavan-Mahdavi et al [ 68 ], and modified surface properties of composite materials were reported by Goiana et al [ 72 ] and Chen et al [ 79 ], where they noted changes in surface morphology and hydrophobicity depending on the type of film and plasma treatment frequency, with improved wettability, roughness, and surface free energy after coating or plasma treatment. Additionally, changes in film structure were observed by Wu et al [ 77 ] and Chen et al [ 47 ], while observing rearrangement of protein chains, slight changes in crystal structure, and improved packing density within the film structure.…”
Section: Plasma Technology In Food Packagingmentioning
confidence: 93%
“…Effect of different chitosan concentrations and plasma treatment durations on fresh pistachios was studied by Akhavan-Mahdavi and co-workers [ 68 ], and the radar chart depicted below provides an in-depth understanding on the sensory analysis results after 180 days of storage of pistachios after the treatments ( Figure 3 ). In their study, the influence of varying amounts of chitosan (0.5 and 1.5% w / v ) and cold plasma treatment duration (60 and 120 s) were observed and reported for 180 days of pistachio storage.…”
Section: Plasma Technology In Food Packagingmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, edible biodegradable films offer desired surface features in addition to excellent mechanical capabilities, barrier properties against gases, water vapor, and moisture [5,6].…”
mentioning
confidence: 99%